Bonusrente statt Zuschussrente - Martin Gasche (Wirtschaftsdienst, 2012)
Das Herzstück des sogenannten Rentenpakets des Bundesministeriums für Arbeit und Soziales ist die Zuschussrente. Sie soll niedrige Renten von Personen mit einem vollen Erwerbsleben aufstocken. Die Analyse zeigt, dass die Zuschussrente mit großen Ungleichbehandlungen und negativen Arbeitsanreizen verbunden ist. Mit der Bonusrente wird ein alternatives Modell vorgeschlagen, das sowohl die Ungleichbehandlungen als auch die Verzerrungen reduziert. – – The 'grant pension' is the most important part of the new German government pension reform plans. The aim of the grant pension is to support people who would otherwise receive only a small public pension despite working their whole lives. The analysis shows that the grant pension would result in some people with nearly identical work histories and equal contribution payments being treated unequally while others with dissimilar work histories and different contribution payments would be treated equally. This leads to negative incentives to work. The 'bonus pension' is presented as an alternative model which reduces the negative effects of the grant pension.
Keywords: H55; 330; Rentenreform; Existenzminimum; Armut; Alte Menschen; Ökonomischer Anreiz; Verteilungswirkung; Deutschland